Perceptions of nurses regarding quality of adult cardiopulmonary resuscitation in Ghana: a qualitative study - Esther Amoako-Mensah; Gloria Achempim-Ansong; Newton Isaac Gbordzoe; Cornelia Esson Adofo; Jacob Owusu Sarfo (BMC, 2023)
Abstract Objectives Cardiopulmonary resuscitation (CPR) is a necessary life-saving emergency intervention for patients with cardiac arrest and other medical conditions. The study's primary objective was to qualitatively explore nurses' perceptions of the quality of adult cardiopulmonary resuscitation in Ghana. Methods An exploratory descriptive qualitative study was conducted among 13 purposively sampled nurses in Ghana. We collected thirteen face-to-face and telephone interviews using a semi-structured interview guide. Data were transcribed verbatim and analysed using the thematic analysis approach recommended by Braun and Clarke. Results Data analysis revealed that nurses were filled with positive emotions when patients regained consciousness following resuscitation. When the otherwise happens, they tend to become tortured psychologically and filled with negative emotions. Besides, environmental factors such as the time of initiating CPR following a cardiac arrest, the availability and appropriateness of equipment and medications, workplace ergonomics, and institutional regulations affected the quality of resuscitation practices of nurses. Participants perceived that attitudes of condemnation, prejudice, apathy and skills deficiency also impacted the quality of resuscitation practices. Significant aspects of self-reported behavioural competence that affected resuscitation were knowledge and skills of CPR, confidence in initiating CPR, and the need for effort maximisation. Conclusion This study revealed several non-medical factors that influenced the resuscitation practices of nurses from their perspective. Nurses need to maximise their effort toward seeking further education in speciality areas such as emergency nursing and critical care nursing to guide their CPR practices and other newly emerging evidence-based protocols.